A journey around the different scales involved in the description of matter and complex systems : a brief overview with special emphasis on kinetic theory approaches /: a brief overview with special emphasis on kinetic theory approaches. ([2018]) - Chinesta, Francisco; Abisset-Chavanne, Emmanuelle
No abstract available